Statistical Analysis of Simulated Spaceborne Thermodynamics Lidar Measurements in the Planetary Boundary Layer - Whiteman, David N.; Di Girolamo, Paolo; Behrendt, Andreas; Wulfmeyer, Volker; Franco, Noemi (Frontiers in Remote Sensing, 2022)
The performance of a spaceborne Raman lidar offering measurements of water vapor, temperature, aerosol backscatter and extinction is assessed statistically by use of a lidar simulator and a global model to provide inputs for simulation. The candidate thermodynamics lidar system is envisioned to make use of a sun-synchronous, dawn/dusk orbit. Cloud-free atmospheric profiles simulated by the NASA/GSFC GEOS model for the orbit of the CALIPSO satellite on July 15, 2009 were used as input to a previously validated lidar simulator where GEOS profiles that satisfy the solar zenith angle restrictions of the dawn/dusk orbit, and are located within the Planetary Boundary Layer as defined by the GEOS model, were selected for the statistical analysis. To assess the performance of the simulated thermodynamics lidar system, measurement goals were established by considering the WMO Observing Systems Capability Analysis and Review (OSCAR) requirements for Numerical Weather Prediction. The efforts of Di Girolano et al., 2018 established the theoretical basis for the current work and discussed many of the technological considerations for a spaceborne thermodynamics lidar. The work presented here was performed during 2017-2018 under the auspices of the NASA/GSFC Planetary Boundary Layer Science Task Group and expanded on previous efforts by considerably increasing the statistical robustness of the performance simulations and extending the statistics to include those of aerosol backscatter and extinction measurements. Further work that is currently being conducted includes Observing Systems Simulation Experiments to assess the impact of a thermodynamics lidar on global forecast improvement.